(untitled) (Cadernos de Sociomuseologia, 2022)
In this text, I present subjective reinterpretations of Freire, in the light of the work with Instituto Paulo Freire de Portugal (IPFP). Speaking from my particular location, I express my voice – experience, knowledge(s), history and expectations of the world – as an individual being inserted in a set of structural locations of power, such as gender, social status, and age. These and other locations of power inform my interpretation and positions as author and actor of my history, with other people and mediated by the world. I start by presenting the construction of my localized view, which builds on experience. And then I move to present the creation of the IPFP and reflectively highlight some of the activities developed by this organization, in the last 20 years. These activities embody our appropriation and reinvention of Freire’s thought. We move within the horizon of the humanizing reconstruction of care, recognition and knowledge, as well as of the societies to which they give – and from which they extract – meanings. With no concern for exhaustiveness, this reflective narrative encompasses specific aspects of the IPFP’s work, which appear inserted in a more global panorama of action and in a work of co-labour with other people of the institute. Key-words: Paulo Freire; Instituto Paulo Freire de Portugal; humanizing reconstruction; reflexive narrative